"J" Rooting of Florida Strawberry Transplants - John R. Duval; Elizabeth A. Golden (EDIS)
Quick establishment of strawberry transplants in Florida is essential because early season yields can determine the success of the growing season. This study was implemented to determine if current planting technique adversely affects strawberry performance. This document is HS990, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 30, 2004.